Efficient Electrocatalyst for Hydrogen Evolution Reaction based on N-rGO-MWCNT/CuAlO2 Nanocomposite in Acidic Media. (29th April 2021) - Arjunan, Karthi keyan; Rajakumaran, Ramachandran; Sakthinathan, Subramanian; Chen, Shen-Ming; Chiu, Te-Wei; Vinothini, Sivaramakrishnan
Abstract : The CuAlO2 delafossite complex was incorporated with nitrogen-doped reduced graphene oxide (N-rGO) and multiwalled carbon nanotubes (MWCNT) based nanocomposite (N-rGO-MWCNT/CuAlO2 ) for the hydrogen evolution reaction (HER). The CuAlO2 delafossite complex was made by self-combustion glycine nitrate process (GNP), and the N-rGO-MWCNT composite was prepared by the hydrothermal method. The morphology was characterized by spectroscopy and microscopy techniques. The materials were structurally well ordered with a porous structure and high surface area. The GCE/N-rGO-MWCNT/CuAlO2 electrode exhibited electrocatalytic activity for the hydrogen evolution reaction (HER) under strongly acidic conditions with a low over-potential, increasing reduction current, and a small Tafel slope of 48 mV dec −1 at 10 mA cm −1 with long-term stability under operating conditions.